ECOLOGICAL GROUPING OF PLANT PHYTONEMATODES - Bakhtiyar Norbekovich Tаshmamatov; Nargiza Eshmamatovna Dzhumanova; Barchina Kamalovna Murodullaeva (American Journals, 2023)
Mesathermal hygrophils are confined to floodplain forests (tugai) of river valleys. In irrigated farming, megathermal hygrophils can transition to a cultural area and cause enormous harm to agriculture. Mesathermal hygrophils include nematode species associated with biotopes with excessive moisture under moderate or cold temperature conditions.